A kind of para-aramid aerogel fiber and preparation method thereof

Through inorganic composite technology, para-aramid polymer and silica aerogel are dissolved and mixed in concentrated sulfuric acid to prepare high-strength, woven para-aramid aerogel fibers, which solves the existing technology The problems of low porosity and poor thermal resistance performance of aerogels have achieved high strength and good thermal resistance performance.

CN119162689BActive Publication Date: 2025-02-25TAYHO ADVANCED MATERIALS GRP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411686624.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

It is difficult to prepare high-strength, woven para-aeramide aerogel fibers, and the aerogel has low porosity and poor thermal resistance.

Method used

Inorganic composite method, para-aramid polymer and silica aerogel are dissolved and mixed in concentrated sulfuric acid, para-aramid primary fibers are prepared by dry spray wet spinning, and replaced in alkali solution and lyophilized. , para-aramid aerogel fiber was obtained.

Benefits of technology

The prepared para-aramid aerogel fiber has high strength, can achieve flexible braidability, and has a larger specific surface area and better thermal resistivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the field of chemical material technology, and specifically to a para-aramid aerogel fiber and a preparation method thereof, wherein the preparation method comprises: S1, dissolving and mixing a para-aramid polymer and a silica aerogel in concentrated sulfuric acid to obtain a para-aramid spinning stock solution; the weight ratio of the para-aramid polymer to the silica aerogel is 1: (0.01-0.05). S2, preparing para-aramid nascent fibers from the para-aramid spinning stock solution by dry-jet wet spinning; S3, washing the para-aramid nascent fibers after replacement in an alkaline solution, and freeze-drying to obtain the para-aramid aerogel fibers. The preparation method of the present invention adopts an inorganic composite method to prepare para-aramid aerogel fibers, which solves the problem that para-aramid has high strength, high modulus, and dense molecular chains but cannot realize an aerogel structure. The prepared para-aramid fiber aerogel has high strength and can realize flexible weavability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a para-aramid aerogel fiber and a preparation method thereof, belonging to the technical field of chemical materials. Background Art

[0002] The full name of para-aramid fiber is poly(p-phenylene terephthalamide) (PPTA), also known as 1414. It is synthesized by low-temperature solution polycondensation of para-phenylenediamine and terephthaloyl chloride, and has the characteristics of high strength and high modulus. Its high strength, high modulus and excellent heat resistance are widely valued by countries around the world. Para-aramid fiber is mostly used as a lightweight, heat-resistant textile structural material or composite structural reinforcement material. It is a rare high-quality material for national defense, military industry and special fields. In the civilian field, it can be used for optical cable communications, river cable-stayed bridge ropes, building reinforcement, car bumpers, aircraft tires, papermaking industry and other purposes.

[0003] Aerogel is a three-dimensional porous material with ultra-high porosity and is one of the synthetic materials with the lowest density known so far. A large number of nano-scale tiny pores give aerogels extremely low apparent density and thermal conductivity. High porosity and specific surface area give aerogels good properties such as light weight, heat insulation, sound insulation and high-efficiency adsorption. Therefore, the development of para-aramid aerogel fibers is of great significance.

[0004] Chinese patent application CN108793943A discloses a method for preparing a photocatalytic silica aerogel fiber product with adjustable hydrophilicity and hydrophobicity modified by graphene oxide. By using graphene oxide to modify silica aerogel / fiber products, its mechanical properties are enhanced, its hydrophilicity and adsorption properties are improved, and fiber products with different hydrophilicity and hydrophobicity can be obtained by adjusting the amount of graphene oxide added and using different modified sol concentrations. However, the preparation method is to immerse the fiber product in the modified sol, and obtain the gel after standing for a period of time; then the semi-finished product of silica aerogel / fiber product modified by graphene oxide is hydrophobically modified and dried to obtain the finished aerogel fiber. This method improves the mechanical properties of aerogel fiber products by adding graphene oxide, the raw material cost is high, and the preparation process is complicated; in addition, it is found in the experiment that fine denier fibers cannot be obtained by this method, and para-aramid aerogel fibers that can be woven cannot be obtained, so it is of great value to develop a method for preparing a para-aramid aerogel fine denier fiber that can be woven.

[0005] Currently available aerogel products are generally in the form of silica composites, which have serious powder loss problems and are difficult to be used in the wearable field. The aerogel fibers currently developed on the market are often of low strength and cannot achieve weaving performance, so they cannot be made into cloth for application. In addition, para-aramid has high rigidity and dense structure, and the aerogel structure is difficult to form. The aerogel has low porosity and poor thermal resistance. Therefore, it is of great significance to develop a para-aramid aerogel fiber with excellent mechanical properties, high porosity and weaving performance. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a para-aramid aerogel fiber and a preparation method thereof, and adopts an inorganic composite method to solve the problem that para-aramid has high strength, high modulus, and dense molecular chains but cannot realize an aerogel structure. The prepared para-aramid fiber aerogel has high strength and can achieve flexible weavability.

[0007] The technical solution of the present invention to solve the above technical problems is as follows: a method for preparing para-aramid aerogel fiber, the preparation method comprising:

[0008] S1, dissolving and mixing a para-aramid polymer and a silica aerogel in concentrated sulfuric acid to obtain a para-aramid spinning solution;

[0009] S2, preparing para-aramid primary fibers by dry-jet wet spinning of the para-aramid spinning stock solution;

[0010] S3. After the para-aramid nascent fibers are replaced in an alkaline solution, they are washed and freeze-dried to obtain the para-aramid aerogel fibers.

[0011] Furthermore, in step S1, the weight ratio of the para-aramid polymer to the silica aerogel is 1:(0.01-0.05).

[0012] Furthermore, in step S1, the inherent viscosity of the para-aramid spinning solution at 25° C. is 6.5-7.2.

[0013] Furthermore, during the dry-jet wet spinning process of step S2, the draft ratio of the spinning coagulation bath is 6-10 times.

[0014] Furthermore, in the dry-jet wet spinning process of step S2, the coagulation bath is a sulfuric acid aqueous solution with a mass concentration of 20-40%, and the coagulation bath temperature is 50-80°C.

[0015] Furthermore, in the dry-jet wet spinning process of step S2, the water washing temperature is 80-100° C.; and the strength of the para-aramid primary fiber is 8-12 cN / dtex.

[0016] Furthermore, in step S3, the para-aramid virgin fiber is replaced in the alkaline solution for 10-12 hours, the alkaline solution is a sodium hydroxide aqueous solution or a potassium hydroxide aqueous solution, and the mass concentration of the alkali in the alkaline solution is 2%-5%.

[0017] Furthermore, the freeze-drying temperature is -40°C to -25°C, the freeze-drying pressure is 8-15Pa, and the freeze-drying time is 48-52h.

[0018] Furthermore, in step S1, the preparation method of the para-aramid polymer is:

[0019] Add p-phenylenediamine to the solvent and control the dissolving temperature to be 80-100°C. After the p-phenylenediamine is dissolved, add terephthaloyl chloride to the reaction system and control the reaction temperature to be 10-30°C. The molar ratio of p-phenylenediamine to terephthaloyl chloride is 1:(0.9-0.98). After the reaction is completed, wash with water and dry to obtain the p-aramid polymer.

[0020] The invention also discloses a para-aramid aerogel fiber, and the para-aramid aerogel fiber is prepared according to the preparation method of the invention.

[0021] The beneficial effects of the present invention are:

[0022] The preparation method of the para-aramid aerogel fiber of the present invention adopts an inorganic composite method to solve the problem that the para-aramid has high strength, high modulus, and dense molecular chains but cannot realize an aerogel structure. The prepared para-aramid fiber aerogel has high strength and can realize flexible weavability.

[0023] The pores of the para-aramid aerogel fiber of the present invention come from the aerogel holes formed by the fiber itself on the one hand, and from the silica aerogel on the other hand, so that the para-aramid aerogel fiber has a larger specific surface area and a better thermal resistivity effect. The para-aramid aerogel fiber has both high thermal resistivity and excellent mechanical properties, and the preparation method can prepare fine-denier para-aramid aerogel fibers, achieving flexible weaving properties, which is more conducive to the application in fabrics. DETAILED DESCRIPTION

[0024] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.

[0026] A method for preparing para-aramid aerogel fiber, characterized in that the preparation method comprises:

[0027] S1, dissolving and mixing the para-aramid polymer and the silica aerogel in concentrated sulfuric acid (mass concentration ≥ 98%) to obtain a para-aramid spinning solution;

[0028] S2, preparing para-aramid primary fibers by dry-jet wet spinning of the para-aramid spinning stock solution;

[0029] S3. After the para-aramid nascent fibers are replaced in an alkaline solution, they are washed and freeze-dried to obtain the para-aramid aerogel fibers.

[0030] Specifically, in step S1, the weight ratio of the para-aramid polymer to the silica aerogel is 1:(0.01-0.05).

[0031] Specifically, in step S1, the inherent viscosity of the para-aramid spinning solution at 25° C. is 6.5-7.2.

[0032] Specifically, in the dry-jet wet spinning process of step S2, the draft ratio of the spinning coagulation bath is 6-10 times.

[0033] Specifically, in the dry-jet wet spinning process of step S2, the coagulation bath is a sulfuric acid aqueous solution with a mass concentration of 20-40%, and the coagulation bath temperature is 50-80°C.

[0034] Specifically, in the dry-jet wet spinning process of step S2, the water washing temperature is 80-100° C.; the strength of the para-aramid primary fiber is 8-12 cN / dtex.

[0035] Specifically, in step S3, the para-aramid virgin fiber is replaced in the alkaline solution for 10-12 hours, the alkaline solution is a sodium hydroxide aqueous solution or a potassium hydroxide aqueous solution, and the mass concentration of the alkali in the alkaline solution is 2%-5%.

[0036] Specifically, the freeze-drying temperature is -40°C to -25°C, the freeze-drying pressure is 8-15Pa, and the freeze-drying time is 48-52h.

[0037] Specifically, in step S1, the preparation method of the para-aramid polymer is:

[0038] Add p-phenylenediamine to the solvent and control the dissolving temperature to be 80-100°C. After the p-phenylenediamine is dissolved, add terephthaloyl chloride to the reaction system and control the reaction temperature to be 10-30°C. The molar ratio of p-phenylenediamine to terephthaloyl chloride is 1:(0.9-0.98). After the reaction is completed, wash with water and dry to obtain the p-aramid polymer.

[0039] More specifically, the solvent is any one of NMP, DMF, DMSO and DMAC.

[0040] More specifically, the silica aerogel particles used in the embodiments of the present invention have a diameter of 2-5 μm.

[0041] A para-aramid aerogel fiber is prepared according to the preparation method of the present invention.

[0042] Example 1

[0043] A method for preparing para-aramid aerogel fiber:

[0044] (1) Preparation of para-aramid polymer:

[0045] Add p-phenylenediamine to DMAC and control the dissolution temperature to 90°C. After the p-phenylenediamine is dissolved, add terephthaloyl chloride to the reaction system and control the reaction temperature to 10°C. The molar ratio of p-phenylenediamine to terephthaloyl chloride is 1:0.9. After the reaction is completed, wash with water and dry to obtain the p-aramid polymer.

[0046] (2) Preparation of para-aramid spinning solution:

[0047] The para-aramid polymer and the silica aerogel are dissolved and mixed in concentrated sulfuric acid to obtain a para-aramid spinning solution; the weight ratio of the para-aramid polymer to the silica aerogel is 1:0.01, and the para-aramid spinning solution has a logarithmic viscosity of 6.5 at 25°C.

[0048] (3) Preparation of para-aramid primary fiber:

[0049] The para-aramid spinning stock solution is used to prepare para-aramid primary fibers through dry-jet wet spinning; wherein the spinning coagulation bath draft ratio is 6 times; the coagulation bath is a sulfuric acid aqueous solution with a mass concentration of 20%, the coagulation bath temperature is 50°C; and the water washing temperature is 85°C.

[0050] (4) Preparation of para-aramid aerogel fibers:

[0051] The para-aramid nascent fiber was replaced in a sodium hydroxide aqueous solution (mass concentration of 5%) for 10 hours, washed with clean water, and freeze-dried to obtain the para-aramid aerogel fiber, wherein the freeze-drying temperature was -40°C, the freeze-drying pressure was 8 Pa, and the freeze-drying time was 48 hours.

[0052] Example 2

[0053] A method for preparing para-aramid aerogel fiber:

[0054] (1) Preparation of para-aramid polymer:

[0055] Add p-phenylenediamine to DMF and control the dissolution temperature to 80°C. After the p-phenylenediamine is dissolved, add terephthaloyl chloride to the reaction system and control the reaction temperature to 12°C. The molar ratio of p-phenylenediamine to terephthaloyl chloride is 1:0.92. After the reaction is completed, wash with water and dry to obtain the p-aramid polymer.

[0056] (2) Preparation of para-aramid spinning solution:

[0057] The para-aramid polymer and the silica aerogel are dissolved and mixed in concentrated sulfuric acid to obtain a para-aramid spinning solution; the weight ratio of the para-aramid polymer to the silica aerogel is 1:0.02, and the para-aramid spinning solution has a logarithmic viscosity of 6.8 at 25°C.

[0058] (3) Preparation of para-aramid primary fiber:

[0059] The para-aramid spinning stock solution is used to prepare para-aramid primary fibers through dry-jet wet spinning; the spinning coagulation bath draft ratio is 7 times; the coagulation bath is a sulfuric acid aqueous solution with a mass concentration of 25%, the coagulation bath temperature is 55°C; and the water washing temperature is 80°C.

[0060] (4) Preparation of para-aramid aerogel fibers:

[0061] The para-aramid nascent fiber was replaced in a potassium hydroxide aqueous solution (mass concentration of 2%) for 12 hours, washed with clean water, and freeze-dried to obtain the para-aramid aerogel fiber, wherein the freeze-drying temperature was -35°C, the freeze-drying pressure was 9 Pa, and the freeze-drying time was 52 hours.

[0062] Example 3

[0063] A method for preparing para-aramid aerogel fiber:

[0064] (1) Preparation of para-aramid polymer:

[0065] Add p-phenylenediamine to DMSO and control the dissolution temperature to 100°C. After the p-phenylenediamine is dissolved, add terephthaloyl chloride to the reaction system and control the reaction temperature to 15°C. The molar ratio of p-phenylenediamine to terephthaloyl chloride is 1:0.94. After the reaction is completed, wash with water and dry to obtain the p-aramid polymer.

[0066] (2) Preparation of para-aramid spinning solution:

[0067] The para-aramid polymer and the silica aerogel are dissolved and mixed in concentrated sulfuric acid to obtain a para-aramid spinning solution; the weight ratio of the para-aramid polymer to the silica aerogel is 1:0.03, and the para-aramid spinning solution has a logarithmic viscosity of 6.9 at 25°C.

[0068] (3) Preparation of para-aramid primary fiber:

[0069] The para-aramid spinning stock solution is used to prepare para-aramid primary fibers through dry-jet wet spinning; wherein the spinning coagulation bath draft ratio is 8 times; the coagulation bath is a sulfuric acid aqueous solution with a mass concentration of 30%, the coagulation bath temperature is 60°C; and the water washing temperature is 100°C.

[0070] (4) Preparation of para-aramid aerogel fibers:

[0071] The para-aramid nascent fiber was replaced in a sodium hydroxide aqueous solution (mass concentration of 4%) for 11 hours, washed with clean water, and freeze-dried to obtain the para-aramid aerogel fiber, wherein the freeze-drying temperature was -30°C, the freeze-drying pressure was 10 Pa, and the freeze-drying time was 48 hours.

[0072] Example 4

[0073] A method for preparing para-aramid aerogel fiber:

[0074] (1) Preparation of para-aramid polymer:

[0075] Add p-phenylenediamine to NMP and control the dissolution temperature to 90°C. After the p-phenylenediamine is dissolved, add terephthaloyl chloride to the reaction system and control the reaction temperature to 18°C. The molar ratio of p-phenylenediamine to terephthaloyl chloride is 1:0.95. After the reaction is completed, wash with water and dry to obtain the p-aramid polymer.

[0076] (2) Preparation of para-aramid spinning solution:

[0077] The para-aramid polymer and the silica aerogel are dissolved and mixed in concentrated sulfuric acid to obtain a para-aramid spinning solution; the weight ratio of the para-aramid polymer to the silica aerogel is 1:0.04, and the para-aramid spinning solution has a logarithmic viscosity of 7.1 at 25°C.

[0078] (3) Preparation of para-aramid primary fiber:

[0079] The para-aramid spinning stock solution is used to prepare para-aramid primary fibers through dry-jet wet spinning; wherein the spinning coagulation bath draft ratio is 9 times; the coagulation bath is a sulfuric acid aqueous solution with a mass concentration of 35%, the coagulation bath temperature is 65°C; and the water washing temperature is 85°C.

[0080] (4) Preparation of para-aramid aerogel fibers:

[0081] The para-aramid nascent fiber was replaced in a potassium hydroxide aqueous solution (mass concentration of 2%) for 10 hours, washed with clean water, and freeze-dried to obtain the para-aramid aerogel fiber, wherein the freeze-drying temperature was -25°C, the freeze-drying pressure was 11 Pa, and the freeze-drying time was 48 hours.

[0082] Example 5

[0083] A method for preparing para-aramid aerogel fiber:

[0084] (1) Preparation of para-aramid polymer:

[0085] Add p-phenylenediamine to DMAC and control the dissolution temperature to 90°C. After the p-phenylenediamine is dissolved, add terephthaloyl chloride to the reaction system and control the reaction temperature to 20°C. The molar ratio of p-phenylenediamine to terephthaloyl chloride is 1:0.95. After the reaction is completed, wash with water and dry to obtain the p-aramid polymer.

[0086] (2) Preparation of para-aramid spinning solution:

[0087] The para-aramid polymer and the silica aerogel are dissolved and mixed in concentrated sulfuric acid to obtain a para-aramid spinning solution; the weight ratio of the para-aramid polymer to the silica aerogel is 1:0.05, and the para-aramid spinning solution has a logarithmic viscosity of 7.0 at 25°C.

[0088] (3) Preparation of para-aramid primary fiber:

[0089] The para-aramid spinning stock solution is used to prepare para-aramid primary fibers through dry-jet wet spinning; the spinning coagulation bath draft ratio is 10 times; the coagulation bath is a sulfuric acid aqueous solution with a mass concentration of 40%, the coagulation bath temperature is 70°C; and the water washing temperature is 90°C.

[0090] (4) Preparation of para-aramid aerogel fibers:

[0091] The para-aramid nascent fiber was replaced in a sodium hydroxide aqueous solution (mass concentration of 4%) for 12 hours, washed with clean water, and freeze-dried to obtain the para-aramid aerogel fiber, wherein the freeze-drying temperature was -38°C, the freeze-drying pressure was 12 Pa, and the freeze-drying time was 48 hours.

[0092] Example 6

[0093] A method for preparing para-aramid aerogel fiber:

[0094] (1) Preparation of para-aramid polymer:

[0095] Add p-phenylenediamine to DMAC, control the dissolution temperature to 90°C, add terephthaloyl chloride to the reaction system after the p-phenylenediamine is dissolved, control the reaction temperature to 25°C, and the molar ratio of p-phenylenediamine to terephthaloyl chloride is 1:0.96. After the reaction is completed, wash with water and dry to obtain the p-aramid polymer.

[0096] (2) Preparation of para-aramid spinning solution:

[0097] The para-aramid polymer and the silica aerogel are dissolved and mixed in concentrated sulfuric acid to obtain a para-aramid spinning solution; the weight ratio of the para-aramid polymer to the silica aerogel is 1:0.025, and the para-aramid spinning solution has a logarithmic viscosity of 7.2 at 25°C.

[0098] (3) Preparation of para-aramid primary fiber:

[0099] The para-aramid spinning stock solution is used to prepare para-aramid primary fibers through dry-jet wet spinning; wherein the spinning coagulation bath draft ratio is 6.5 times; the coagulation bath is a sulfuric acid aqueous solution with a mass concentration of 28%, the coagulation bath temperature is 75°C; and the water washing temperature is 85°C.

[0100] (4) Preparation of para-aramid aerogel fibers:

[0101] The para-aramid nascent fiber was replaced in a sodium hydroxide aqueous solution (mass concentration of 4%) for 11 hours, washed with clean water, and freeze-dried to obtain the para-aramid aerogel fiber, wherein the freeze-drying temperature was -33°C, the freeze-drying pressure was 13 Pa, and the freeze-drying time was 48 hours.

[0102] Example 7

[0103] A method for preparing para-aramid aerogel fiber:

[0104] (1) Preparation of para-aramid polymer:

[0105] p-phenylenediamine is added to DMAC, and the dissolution temperature is controlled at 90°C. After the p-phenylenediamine is dissolved, terephthaloyl chloride is added to the reaction system, and the reaction temperature is controlled at 28°C. The molar ratio of p-phenylenediamine to terephthaloyl chloride is 1:0.98. After the reaction is completed, the p-aramid polymer is obtained by washing with water and drying.

[0106] (2) Preparation of para-aramid spinning solution:

[0107] The para-aramid polymer and the silica aerogel are dissolved and mixed in concentrated sulfuric acid to obtain a para-aramid spinning solution; the weight ratio of the para-aramid polymer to the silica aerogel is 1:0.035, and the para-aramid spinning solution has a logarithmic viscosity of 6.7 at 25°C.

[0108] (3) Preparation of para-aramid primary fiber:

[0109] The para-aramid spinning stock solution is used to prepare para-aramid primary fibers through dry-jet wet spinning; wherein the spinning coagulation bath draft ratio is 7.5 times; the coagulation bath is a sulfuric acid aqueous solution with a mass concentration of 38%, the coagulation bath temperature is 80°C; and the water washing temperature is 85°C.

[0110] (4) Preparation of para-aramid aerogel fibers:

[0111] The para-aramid nascent fiber was replaced in a sodium hydroxide aqueous solution (mass concentration of 4%) for 10 hours, washed with clean water, and freeze-dried to obtain the para-aramid aerogel fiber, wherein the freeze-drying temperature was -28°C, the freeze-drying pressure was 14 Pa, and the freeze-drying time was 48 hours.

[0112] Example 8

[0113] A method for preparing para-aramid aerogel fiber:

[0114] (1) Preparation of para-aramid polymer:

[0115] Add p-phenylenediamine to DMAC and control the dissolution temperature to 90°C. After the p-phenylenediamine is dissolved, add terephthaloyl chloride to the reaction system and control the reaction temperature to 30°C. The molar ratio of p-phenylenediamine to terephthaloyl chloride is 1:0.93. After the reaction is completed, wash with water and dry to obtain the p-aramid polymer.

[0116] (2) Preparation of para-aramid spinning solution:

[0117] The para-aramid polymer and the silica aerogel are dissolved and mixed in concentrated sulfuric acid to obtain a para-aramid spinning solution; the weight ratio of the para-aramid polymer to the silica aerogel is 1:0.045, and the para-aramid spinning solution has a logarithmic viscosity of 6.6 at 25°C.

[0118] (3) Preparation of para-aramid primary fiber:

[0119] The para-aramid spinning stock solution is used to prepare para-aramid primary fibers through dry-jet wet spinning; wherein the spinning coagulation bath draft ratio is 9.5 times; the coagulation bath is a sulfuric acid aqueous solution with a mass concentration of 32%, the coagulation bath temperature is 73°C; and the water washing temperature is 80°C.

[0120] (4) Preparation of para-aramid aerogel fibers:

[0121] The para-aramid nascent fiber was replaced in a sodium hydroxide aqueous solution (mass concentration of 4%) for 10 hours, washed with clean water, and freeze-dried to obtain the para-aramid aerogel fiber, wherein the freeze-drying temperature was -26°C, the freeze-drying pressure was 15 Pa, and the freeze-drying time was 48 hours.

[0122] Comparative Example 1

[0123] The para-aramid aerogel fiber was prepared by the same method as in Example 1, except that the amount of silica aerogel was increased. The weight ratio of the para-aramid polymer to the silica aerogel in this comparative example 1 was 1:0.08.

[0124] Comparative Example 2

[0125] The para-aramid aerogel fiber was prepared by the same method as in Example 1, except that the concentration of the coagulation bath was increased. In Comparative Example 2, the coagulation bath was a sulfuric acid aqueous solution with a mass concentration of 50%.

[0126] Comparative Example 3

[0127] The para-aramid aerogel fiber was prepared by the same method as in Example 1, except that the coagulation bath temperature was lowered. In Comparative Example 3, the coagulation bath temperature was 40°C.

[0128] Comparative Example 4

[0129] The para-aramid aerogel fiber was prepared by the same method as in Example 1, except that the concentration of the coagulation bath was reduced. In this comparative example 4, the coagulation bath was a sulfuric acid aqueous solution with a mass concentration of 15%.

[0130] Comparative Example 5

[0131] The para-aramid aerogel fiber was prepared by the same method as in Example 1, except that the coagulation bath temperature was increased. In this comparative example 5, the coagulation bath temperature was 90°C.

[0132] Comparative Example 6

[0133] The para-aramid aerogel fiber was prepared by the same method as in Example 1, except that the freeze-drying temperature was increased. In Comparative Example 6, the freeze-drying temperature was -15°C.

[0134] Comparative Example 7

[0135] The para-aramid aerogel fiber was prepared by the same method as in Example 1, except that step (1) was changed to using the para-aramid fiber to peel off into a slurry solution, and then adding the silica aerogel. The specific preparation process is as follows:

[0136] Para-aramid fiber (Typron para-aramid 629T) was dissolved in a DMSO solution of potassium hydroxide (the mass concentration of potassium hydroxide was 5%) to obtain a spinning slurry, wherein the solid content of the spinning slurry was 3-5%. Silica aerogel was added to the spinning slurry, wherein the weight ratio of para-aramid fiber to silica aerogel was 1:0.01.

[0137] Then the spinning slurry with silica aerogel was wet spun to prepare para-aramid aerogel fiber. The experiment found that the fiber broke severely during the spinning process and spinning could not be achieved.

[0138] The properties of the para-aramid aerogel fibers prepared in the above examples and comparative examples were tested using the BET test method. The specific test results are shown in Table 1 below.

[0139] Table 1 Performance test data of para-aramid aerogel fiber

[0140]

[0141] It can be seen from the data in the above table that: Example 1 to Example 9, the para-aramid aerogel fibers prepared by the preparation method of the present invention have a larger specific surface area, so that the thermal resistivity effect is higher. The para-aramid aerogel fibers have both high thermal resistivity and excellent mechanical properties. Moreover, the preparation method can prepare fine-denier para-aramid aerogel fibers, which can achieve flexible weaving properties, and thus are more conducive to application in some wearable fabrics with thermal insulation requirements.

[0142] From the comparison of the data of Comparative Example 1 and Example 1, it can be seen that if the dosage ratio of the silica aerogel is increased, the spinneret will be blocked due to excessive addition, resulting in the inability to prepare the para-aramid aerogel fiber.

[0143] From the comparison of the data of Comparative Example 2 and Example 1, it can be seen that: if the concentration of the coagulation bath increases, the strength performance and specific surface area of ​​the para-aramid aerogel fiber will decrease, because the increase in the concentration of the coagulation bath will cause the coagulation speed of the fiber to decrease, resulting in more silica aerogel escaping during the coagulation bath process, and ultimately causing the specific surface area of ​​the para-aramid aerogel fiber to decrease. At the same time, the escape of silica aerogel will also cause unevenness in the para-aramid aerogel fiber, ultimately affecting its strength performance.

[0144] From the comparison of the data of Comparative Example 3 and Example 1, it can be seen that if the coagulation bath temperature is reduced, the strength performance and specific surface area of ​​the para-aramid aerogel fiber will decrease, because the reduction of the coagulation bath temperature will reduce the coagulation speed of the fiber, resulting in more silica aerogel escaping during the coagulation bath process, which ultimately leads to a decrease in the specific surface area of ​​the para-aramid aerogel fiber. At the same time, the escape of silica aerogel will also cause unevenness in the para-aramid aerogel fiber, which ultimately affects its strength performance.

[0145] From the comparison of the data of Comparative Examples 4-5 and Example 1, it can be seen that if the coagulation bath concentration is reduced or the coagulation bath temperature is increased, the strength performance and specific surface area of ​​the para-aramid aerogel fiber will also decrease, because the reduction of the coagulation bath concentration or the increase of the coagulation bath temperature will accelerate the fiber forming speed. If the fiber forming speed is too fast, it will affect the uniformity of the para-aramid aerogel fiber, and ultimately lead to a decrease in strength performance and specific surface area.

[0146] From the comparison of the data of Comparative Example 6 and Example 1, it can be seen that if the freeze-drying temperature is increased, the specific surface area of ​​the para-aramid aerogel fiber will decrease, and the pores in the para-aramid aerogel fiber will be unevenly distributed and sized, which will eventually lead to a decrease in the mechanical properties of the para-aramid aerogel fiber. Therefore, the freeze-drying conditions specified in the present invention are more conducive to obtaining high-quality para-aramid aerogel fibers with excellent performance.

[0147] From the comparison of the data of Comparative Example 8 and Example 1, it can be seen that if the conventional method is used to add silica aerogel after stripping the aramid fiber, fine denier para-aramid aerogel fiber cannot be prepared, because the prepared spinning solution has a low solid content and cannot be formed in the coagulation bath, and due to the repeated dissolution process, the molecular chain structure of the polymer is destroyed, resulting in the inability to prepare aramid aerogel fiber.

[0148] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0149] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.

Claims

1. A method for preparing para-aramid aerogel fiber, characterized in that: The preparation method is: S1, dissolving and mixing a para-aramid polymer and a silica aerogel in concentrated sulfuric acid to obtain a para-aramid spinning solution; S2, preparing para-aramid primary fibers by dry-jet wet spinning of the para-aramid spinning stock solution; S3, after the para-aramid nascent fiber is replaced in an alkaline solution, it is washed and freeze-dried to obtain the para-aramid aerogel fiber; the freeze-drying temperature is -40°C to -25°C, the freeze-drying pressure is 8-15Pa, and the freeze-drying time is 48-52h; In step S1, the preparation method of the para-aramid polymer is: Add p-phenylenediamine to the solvent, control the dissolution temperature to be 80-100°C, add terephthaloyl chloride to the reaction system after the p-phenylenediamine is dissolved, control the reaction temperature to be 10-30°C, and the molar ratio of p-phenylenediamine to terephthaloyl chloride is 1:(0.9-0.98), and after the reaction is completed, wash with water and dry to obtain the p-aramid polymer; In the dry-jet wet spinning process of step S2, the coagulation bath is a sulfuric acid aqueous solution with a mass concentration of 20-40%, and the coagulation bath temperature is 50-80°C.

2. The method for preparing para-aramid aerogel fiber according to claim 1, characterized in that: In step S1, the weight ratio of the para-aramid polymer to the silica aerogel is 1:(0.01-0.05).

3. The method for preparing para-aramid aerogel fiber according to claim 1, characterized in that: In step S1, the inherent viscosity of the para-aramid spinning solution at 25° C. is 6.5-7.

2.

4. The method for preparing para-aramid aerogel fiber according to claim 1, characterized in that: During the dry-jet wet spinning process of step S2, the draft ratio of the spinning coagulation bath is 6-10 times.

5. The method for preparing para-aramid aerogel fiber according to claim 1, characterized in that: In the dry-jet wet spinning process of step S2, the water washing temperature is 80-100° C.; the strength of the para-aramid primary fiber is 8-12 cN / dtex.

6. The method for preparing para-aramid aerogel fiber according to claim 1, characterized in that: In step S3, the para-aramid virgin fiber is replaced in the alkaline solution for 10-12 hours, the alkaline solution is a sodium hydroxide aqueous solution or a potassium hydroxide aqueous solution, and the mass concentration of the alkali in the alkaline solution is 2%-5%.

7. A para-aramid aerogel fiber, characterized in that: The para-aramid aerogel fiber is prepared according to the preparation method according to any one of claims 1-6.

Citation Information

Patent Citations

  • Preparation method of oxidized graphene modified silicon dioxide aerogel fiber product adjustable in hydrophobic and hydrophilic property

    CN108793943A

  • Aerogel composite fiber material as well as preparation method and application thereof

    CN112981575A

  • Preparation method of aromatic polyamide aerogel fiber

    CN115522285A